Principles of Mathematical Induction

1. FIRST PRINCIPLE OF MATHEMATICAL INDUCTION

The proof of proposition by mathematical induction consists of the following three steps :
Step I : (Verification step) : Actual verification of the proposition for the starting value “i
Step II : (Induction step) : Assuming the proposition to be true for “k”, ki and proving that it is true for the value (k + 1) which is next higher integer.
Step III : (Generalization step) : To combine the above two steps Let p(n) be a statement involving the natural number n such that
(i) p(1) is true i.e. p(n) is true for n = 1.

(ii) p(m + 1) is true, whenever p(m) is true i.e. p(m) is true ⇒ p(m + 1) is true.
Then p(n) is true for all natural numbers n.

2. SECOND PRINCIPLE OF MATHEMATICAL INDUCTION

The proof of proposition by mathematical induction consists of following steps :
Step I : (Verification step) : Actual verification of the proposition for the starting value i and (i + 1).
Step II : (Induction step) : Assuming the proposition to be true for k – 1 and k and then proving that it is true for the value k + 1; k i + 1.
Step III : (Generalization step) : Combining the above two steps.
Let p(n) be a statement involving the natural number n such that
(i) p(1) is true i.e. p(n) is true for n = 1 and
(ii) p(m + 1) is true, whenever p(n) is true for all n, where inm
Then p(n) is true for all natural numbers.
For a b, The expression anbn is divisible by
(a) a + b if n is even.                               (b) ab is n if odd or even. 

3. SOME USEFUL FORMULAS

Here are some formulas for sequences that are great for practicing proofs by induction. For any natural number n

  • 1 + 2 + 3+….+ n = n(n+1)2
  • 1 + 3 + 5 + … + (2n-1) = n2
  • 1 + 2 + 22 + … + 2n = 2n+1 – 1
  • 12 + 22 + 32 + … + n2 = n(n+1)(2n+1)6
  • 13 + 23 + 33 + … + n3 = [n(n+1)/2]2
  • 1*2 + 2*3 + … + n(n + 1) = n(n+1)(n+2)3
  • 12 + 32 + 52 + … + (2n + 1)2 = (n+1)(2n+1)(2n+3)3

Illustration -1
The value of 11.2.3+12.3.4++1n(n+1)(n+2) is

(A) n(n+1)2      (B) n(n+1)(2n+1)6        (C) n(n+3)4(n+1)(n+2)       (D) none of these

Solution

(C)

Let P(n) 11.2.3+12.3.4+..+1n(n+1)(n+2)=n(n+3)4(n+1)(n+2)

P(1)=11.2.3=16 on the L.H.S; on the R.H.S =1(1+3)4(1+1)(1+2)=16

P(1) is true

Let P(k) be true.

11.2.3+12.3.4+..+1k(k+1)(k+2)=k(k+3)4(k+1)(k+2)

P(k + 1) on the L.H.S.

= 11.2.3+12.3.4+..+1k(k+1)(k+2)+1(k+1)(k+2)(k+3)

The sum within the square brackets is P(k) which equals k(k+3)4(k+1)(k+2)

P(k + 1) = k(k+3)4(k+1)(k+2)+1(k+1)(k+2)(k+3)=14(k+1)(k+2)k(k+3)2+4(k+3)

= 14(k+1)(k+2)(k+3)(k+1)2(k+4)=(k+1)(k+4)4(k+2)(k+3).

Which is the desired R.H.S. of P(k+1) . Hence, P(k+1) is true.

Hence, by mathematical induction, the result is true for all n.

Illustration -2

The value of 1122113211(n+1)2 is, nN

(A) n14           (B) n+22n+2        (C) nn16       (D) n+24n+1

Solution

(B)

Let P(n) 1122113211(n+1)2=n+22n+2

L.H.S. of P(1) =  1122=34 = R.H.S

Hence P(1) is true.

Assume that P(k) is true.

1122113211(k+1)2=k+22k+2

For P(k + 1), the L.H.S. becomes

11221132.11(k+1)211(k+2)2

= P(k)11(k+2)2=k+22k+2k2+4k+3(k+2)2

= k+22k+2(k+1)(k+3)(k+2)2=(k+2)(k+1)(k+3)2(k+1)(k+2)2

=k+32(k+1)+2P(k+1) is true 

Hence, by mathematical induction, the result is true for all n ∈ N

Illustration -3

The smallest positive integer n, for which n!<n+12n hold is

(A) 1         (B) 2          (C) 3            (D) 4

Solution

(B)

Let P(n) : n!<n+12n

Step I: For n = 2  2!<2+1222<94

⇒ 2 < 2.25 which is true. Therefore, P(2) is true.

Step II: Assume that P(k) is true, then P(k): k!<k+12k

Step III: For n = k + 1, P(k + 1): (k + 1)! < k+22k+1

k!<k+12kk+1k!<(k+1)k+12k

⇒ (k + 1)k!  (k+1)k+12k  ___________________ (i)

and   (k+1)k+12k<k+22k+1   ___________________ (ii)

k+2k+1k+1>21+1k+1k+1>2

1+(k+1)1k+1+k+C211k+12+.>2

1+1+C2k+11k+12+.>2

Which is true, hence (ii) is true.

From (i) and (ii),  (k+1)!<(k+1)k+12k<k+22k+1(k+1)!<k+22k+1

Hence P(k+1) is true. Hence by the principle of mathematical induction P(n) is true for all n∈N

Trick: By check options,

(A) For n = 1,  1!<1+121 1 < 1 which is wrong

(B) For n = 2, 2!<3222<94  which is correct

(C) For n = 3,  3!<3+123 6 < 8 which is correct

(D) For n = 4, 4!<4+12424<524

⇒ 24 < 39.0625 which is correct.

But smallest positive integer n is 2.

Illustration -4

Let S(k) = 1 + 3 + 5 + … + (2k – 1) = 3 + k2. Then which of the following is true.

(A) Principle of mathematical induction can be used to prove the formula

(B) S(k) ⇒ S(k+1)

(C) S(k)  S(k+1)

(D) S(1) is correct

Solution

(C)

We have S(k) = 1 + 3 + 5 + ….+ (2k – 1) = 3 + k2,

S(1) ⇒ 1 = 4, Which is not true and S(2) ⇒ 3 = 7, Which is not true. Hence induction cannot be applied and S(k)  S(k + 1).

Illustration -5

Given  Un+1=3Un2Un1 and U0=2, U1=3, the value of Un for all n∈N is

(A) 2n1             (B)  2n+1                       (C) 0          (D) None of these

Solution

(B)

Un+1=3Un2Un1…..(i)

Step I : Given U1=3

For n =1,  U1+1=3U12U0, U2=3.32.2=5,

Option (b) Un=2n+1

For n = 1, U1=21+1=3 which is true. For n = 2, U2=22+1=5 which is true

Therefore, the result is true for n = 1 and n = 2

Step II : Assume it is true for n = k then it is also true for n = k – 1

Then  Uk=2k+1    …..(ii) and  Uk1=2k1+1  …..(iii)

Step III : Putting n = k in (i), we get

Uk+1=3Uk2Uk1=32k+122k1+1

= 3.2k+32.2k12=3.2k+12.2k1

3.2k2k+1=2.2k+1=2k+1+1

  Uk+1=2k+1+1

This shows that the result is true for n=k+1, by the principle of mathematical induction the result is true for all n∈N.

Illustration -6

Prove the following by using the principle of mathematical induction for all n ∈ N:

13 + 23 + 33 + …. + n3 = n(n1)22

Solution

Let the given statement be P(n), i.e.,

P(n): 13 + 23 + 33 + …. + n3 = n(n+1)22

For n = 1, we have

P(1): 13 = 1 = 1(1+1)22=1.222=12=1,  which is true.

Let P(k) be true for some positive integer k, i.e.,

13 + 23 + 33 + ….. + k3 = k(k+1)22 __________ (i)

We shall now prove that P(k + 1) is true.

Consider

13 + 23 + 33 + … + k3 + (k + 1)3 =k(k+1)22+(k+1)3     [Using (i)]

=k2(k+1)24+(k+1)3

=k2(k+1)2+4(k+1)34

=(k+1)2k2+4(k+1)4

=(k+1)2k2+4k+44

=(k+1)2(k+2)24

=(k+1)2(k+1+1)22

=(k+1)(k+1+1)22

Thus, P(k + 1) is true whenever P(k) is true.

Hence, by the principle of mathematical induction, statement P(n) is true for all natural numbers i.e., n.

Illustration -7

Prove the following by using the principle of mathematical induction for all n ∈ N:

12 + 32 + 52 + … + (2n – 1)2 = n(2n1)(2n+1)3

Solution

Let the given statement be P(n), i.e.,

P(n) = 12 + 32 + 52 + … + (2n – 1)2 = n(2n1)(2n+1)3

For n = 1, we have

P(1) = 12 = 1 = 1(2.11)(2.1+1)3=1.1.33=1, which is true.

Let P(k) be true for some positive integer k, i.e.,

P(k) = 12 + 32 + 52 + … + (2k – 1)2 = k(2k1)(2k+1)3  _____________ (1)

We shall now prove that P(k + 1) is true.

Consider

{12 + 32 + 52 + … + (2k – 1)2} + {2(k + 1) – 1}2

=k(2k1)(2k+1)3+(2k+21)2    [Using (1)]

=k(2k1)(2k+1)3=(2k+1)2

=k(2k1)(2k+1)+3(2k+1)23

=(2k+1){k(2k1)+3(2k+1)}3

=(2k+1)2k2k+6k+33

=(2k+1)2k2+5k+33

=(2k+1)2k2+2k+3k+33

=(2k+1){2k(k+1)+3(k+3)}3

=(2k+1)(k+1)(2k+3)3

=(k+1){2(k+1)1}{2(k+1)+1}3

Thus, P(k + 1) is true whenever P(k) is true.

Hence, by the principle of mathematical induction, statement P(n) is true for all natural numbers i.e., n.

4. DIVISIBILITY PROBLEMS

To show that an expression is divisible by an integer

(i) If a, p, n, r are positive integers, then first of all we write apn+r=apn·ar=apn·ar.

(ii) If we have to show that the given expression is divisible by c.

Then express, ap=1+ap1, if some power of ap1 has c as a factor.

ap=2+ap2, if some power of ap2 has c as a factor.

ap=K+apK, if some power of apK has c as a factor.

Illustration -8

For every natural number n, 11n+2 + 122n+1 is divisible by

(A) 133                          (B) 123                 (C) 91                (D) none of these

Solution

(A).

Let P(n) = 11n+2 + 122n+1

P(1) = 113 + 123 = 3059 which is divisible by 133.

Let P(k) = 11k+2 + 122k+1 be divisible by 133.

P(k+1) = 11k+3 + 122k+3  = 11k+2.11 + 122k+1 144,

= 11.11k+2 + (133 + 11) 122k+1

= 11[11k+2 + 122k+1] + 133.122k+1

= 11.P(k) + 133.122k+1

P(K) is divisible by 133 also 133.122k+1 is divisible by 133. Hence, P (k + 1) is also divisible by 133. Hence, by mathematical induction, the result is true for all n.

Illustration -9

For every natural number n, 52n + 2 –24n – 25 is divisible by

(A) 502                          (B) 223                 (C) 471                   (D) 576

Solution

(D)

Let P (n) = 52n + 2 –24n –25

Then P (1) = 54 –24 –25 = 576

Then P (1) is divisible by 576

Now assume that P (k) is divisible by 576, that is assume

P (k) = 52k + 2 – 24k – 25 = 576m        ……(1)

where m is a positive integer.

P (k + 1) = 52(k + 1) + 2 – 24(k + 1) – 25 = 52.52k + 2 – 24k – 49

= 25[52k + 2 – 24k – 25] + 25.24k + 25.25 – 24k – 49 = 25P (k) + 576k + 576

= 25.576m + 576(k + 1)  by (1)  = 576(25m + k + 1)

Hence P (k + 1) is divisible by 576.

Hence by mathematical induction, the result is true for all n.

Illustration -10

(1+x)nnx1 is divisible by (where n ∈ N)

(A) 2x            (B) x2          (C) 2x3              (D) All of these

Solution

(B)

(1+x)n=1+nx+n(n1)2!x2+n(n1)(n2)3!x3+..

(1+x)nnx1=x2n(n1)2!+n(n1)(n3)3!x+..

From above it is clear that (1+x)nnx1 is divisible by x2.

Trick: (1+x)nnx1. Put n=2 and x=3;  Then 422.31=9

Is not divisible by 6, 54 but divisible by 9. Which is given by option (c) = x29.

Illustration -11

The greatest integer which divides the number 1011001 is

(A) 100                          (B) 1000               (C) 10000           (D) 100000

Solution

(C)

(1+100)100=1+100·100+100.991.2(100)2+

1011001=100.1001+100.991.2+100.99.983.2.1100+..

From above it is clear that, 1001001 is divisible by  (100)2=10000

5. APPLICATIONs OF MATHEMATICAL INDUCTION

  SOME IMPORTANT POINTS

1. A.P. Series : a + (a + d) + (a + 2d) +……….

i) nth term = a+(n1)d=tn=SnSn1

ii) Sum of first n terms of an A.P.

= Sn=tn=n2[2a+(n1)d] (where a is first term, d is common difference of an A.P.)

2. G.P. Series : a + ar + ar2 + ar3 +……..

i) nth term = tn=a.rn1

ii) Sum of first n terms = Sn=arn1r1 if r>1

                                                      =a1rn1r if r<1

iii) Sum of infinite terms = S=a1r(|r|<1)

3. Arithmetico – Geometric series (A.G.P.) :

a+(a+d).r+(a+2d).r2+…….+(a+(n – 1)d).rn-1

i) nth term of the series = tn=a+(n1)d).rn1

ii) Sum of n terms = Sn=a1r+dr1rn1(1r)2(a+n1¯d)rn(1r)

iii) Sum of infinite terms = S=a1r+dr(1r)2,|r|<1

4. 1a(a+d)+1(a+d)(a+2d)+..+1(a+(n1)d)(a+nd)+..

i) 1{a+(n1)d}(a+nd)tn=nth term 

ii) sum of n terms = Sn=1d1a1a+nd=na(a+nd)

5. For a sequence, T1,T2,T3,T4,

the differnece of consecutive terms T2T1,T3T2,T4T3 etc..  are in A.P or G.P then nth term of given series are in the form of an2+bn+c  or  a.rn+b where a, b, c to be determined.

6. In finding nth term of the series, in the suitable option

n = 1 gives the Ist term of the series

n = 2 gives the IInd term of series.

7. In finding the sum of n terms of the series in the suitable option

n=1 gives the Ist term of the series

n=2 gives the sum of first 2 terms of the series

n=3 gives the sum of first 3 terms of the series.

8. To test the divisibility of the given expression put n = 1 and n = 2 in the given expression and get their values and G.C.D or H.C.F. of these two values gives the required divisor.

9. If the series is given upto n terms then begin the verification with n = 1, if the series is given upto (n – 1) terms, then begin the verification with n = 2. If the series is given upto (n – 2) terms, then begin the verification with n=3 etc.

10. cosα+cos(α+β)+cos(α+2β)+++cos(α+(n1)β) = sin(nβ/2)sin(β/2)×cosα+(n1)β/2

11. cosα·cos2α·cos4αcos2n1α = sin2nα2nsinα

12. 1+311+541+791+2n+1n2=(n+1)2

13. The sum of cubes of three consecutive natural numbers is always divisible by 9

14. For all positive integral values of n , xnyn is divisible by x – y.

15. For all positive integral values of n, x2n+1+y2n+1 is divisible by x + y.

16. For all positive integral values of n, x2n1+y2n1is divisible by x + y.

17. Pn+1+(P+1)2n1is divisible by P2+P+1,n2

18. npn is divisible by Pn2 where P is prime.

19. n is any odd integer then nn21 is divisible by 24.

20. The product of “n” consecutive natural numbers is  always divisible by n!.

21. If x, y, m are positive integers then x is said to be congruent of y modulo m if x – y is divisible by m and is denoted by xy(modm)

22. Suppose it is given F(n) > G(n) or F(n)G(n)>1

We have to prove that

F(n +1 ) > G(n + 1) or F(n+1)G(n+1)>1

or  F(n+1)G(n+1)>F(n)G(n)>1 or F(n+1)F(n)G(n)G(n+1)>1.

Illustration -12

For all n ∈ N, 2nCn

(A) < 4n          (B) > 4n       (C) > 2n + 1       (D) none of these

Solution

(A)

To show 2nCn < 4n

F(n) = 4n,   G(n) = 2nCn

F(n+1) = 4n+1,   G(n+1) = 2n+2Cn+1

F(n+1)F(n)·G(n)G(n+1)=4n+14n·Cn2nCn+12n+2

= 4. (2n)!n!n!·(n+1)!(n+1)2n+1=2·(n+1)(2n+1)>1.  ( since  2n + 2 > 2n + 1 )

F(n+1)G(n+1)·G(n)F(n)>1 or F(n+1)G(n+1)>F(n)G(n)>1F(n+1)>G(n+1)

Illustration -13

For all-natural numbers n greater than 1, the value of 1+14+..+1n2

(A)  2n1n        (B)  2n1n       (C) <21n        (D) >1n

Solution

(C). For n = 2,

LH.S=1+14=54 and RH.S.=212=32

54<32 Hence it holds for n = 2.

Assume the result to hold for n = k

1+14+19+.+1k2<21k

For n = k+1, 1+14+19+.+1k2+1(k+1)2<21k+1(k+1)2

Now, if we show that

21k+1(k+1)2<21(k+1)

1k1(k+1)2>1(k+1) then we are through.

1k1(k+1)21k+1>0(k+1)2kk(k+1)k(k+1)2

=k2+2k+1kk2kk(k+1)2=1k(k+1)2>0

Hence the result is true for n = k + 1.

Hence, by mathematical induction, the result is true for all n.

Illustration -14

For what natural number n, the inequality 2n > 2n + 1 is valid?

(A) n 3               (B) n > 1                      (C) n = 2               (D) n > 5

Solution

(A)

For n = 1, 2 < 2 + 1

n = 2, 4 < 5

n = 3, 8 > 7

so the result is true for n = 3

assume the result is true for n = k > 3, i.e.

2k > 2k + 1

So, P (k + 1) = 2k + 1 = 2.2k > 2.(2k + 1) = 4k + 2

= [2(k + 1) + 1] + (2k –1) > 2(k + 1) + 1 as 2k –1 > 0, since k > 3

∴ The result is true for n = k + 1

∴ By the principal of mathematical induction, the result holds n3.

Illustration -15

If x + y = a + b, x2 + y2 = a2 + b2, then xn + yn = an + bn

(A) nN             (B) n 4      (C) n 3          (D) none of these

Solution

(A)

Let P(n) xn + yn = an + bn

P(1) x + y = a + b      … (1)

P(2) x2 + y2 = a2 + b2   … (2)

Hence P(1) and P(2) are true.  Assume the result to be true for n k.

⇒ x k – 1 + yk – 1 = ak – 1 + bk – 1 and xk + yk = ak + bk

In order to prove that P(k + 1) is true, we write

xk + 1 + yk + 1 = x(ak + bk – yk) + y(ak + bk – xk)

= (ak + bk) (x + y) – xy (xk – 1 + yk – 1)

= (ak + bk) (a + b) – xy (ak – 1 + bk – 1)

Now from (1) and (2) xy = ab ⇒ xk + 1 + yk + 1 = ak + 1 + bk +1

which is the desired R.H.S. for P(k + 1).

Hence, by mathematical induction, the result is true for all n.

Illustration -16

If u1 = cos θ, u2 = cos 2θ and un = 2un –1 cosθ – un –2 for n > 2. Then un

(A) tan nθ        (B) cot nθ         (C) sin nθ                 (D) cos nθ  

Solution

(D)

We have to prove that un = cos nθ n N

Clearly u1 = cos θ, u2 = cos 2θ

So the result is true for n = 1 and n = 2  …(1)

Now assume the result for 2 < n k …(2)

Then uk + 1 = 2ukcosθ – uk –1

= 2 cos kθ cosθ – cos (k –1)θ         Using (2)

= cos (k + 1)θ + cos (k –1)θ –cos (k –1)θ = cos (k + 1)θ      …(3)

Hence the result is true for n = k + 1

Hence by mathematical induction the result is true for all n ∈ N.

Illustration -17

Let  Im=0π1cosmx1cosxdx, use mathematical induction, Im

(A) (m1)π4, m=0,1,2,      (B) (m1)π3, m=0,1,2,   

(C), mπ2 = 0, 1, 2…                   (D) mπ, m = 0, 1, 2 …

Solution

(D). l1=0π1cosx1cosxdx=π

I2=0π1cos2x1cosxdx=20π(1+cos2x)dx=2π

The result is true for m = 1, 2. Let the result be true for m k.

Now, 2Ik – Ik – 1 – Ik + 1

= 0π2(1coskx)[1cos(k1)x][1cos(k+1)x](1cosx)dx

= 0π[cos(k1)xcoskx]+[cos(k+1)xcoskx]2sin2(x/2)dx

= 022sinx2sin2k12xsin2k+12x2sin2x2dx = 0π2sinx2×2sinx2coskx2sin2x2dx

= 0πcoskx dx=0Ik+1=2IkIk1=(k+1)π

⇒ The result is true for m = k + 1.

Hence, by mathematical induction, the result is true for all n.

Was this article helpful to you? Yes No